단어 임베딩을 이용한 사진 유사도 평가 및 가상현실기반 인지재활 시스템 - 최권택(KwonTaeg Choi) (디지털콘텐츠학회논문지, 2019)
고령화에 따른 치매 노인의 증가로 사회 및 경제적 비용이 크게 증가해 이를 해결하기위한 연구가 이루어지고 있다. 본 논문은 치대 대상자의 기억과 추억이 반영되어 있는 사진들을 수집해 영상 인식 기술과 군집화 알고리즘을 사용한 가상현실 기반의 인지 재활 시스템을 제안한다. 기존의 객관적인 사진이나 그림을 사용하는 방법을 탈피해 개인의 경험과 추억을 가상현실 공간에 재현하는 융합 콘텐츠라는 점에서 기존 방법과 구별된다. 사진 2022장을 실험 데이터 셋으로 사용해 제안하는 군집화 알고리즘의 효율성을 평가하였다. 사진 영상을 의미 기반의 단어벡터로 표현해 군집화 함으로써 문맥적으로 유사한 사진들이 군집화되는 것을 확인했다. 또한 가우시안 혼합모델로부터 최소 거리가 유지되도록 사진을 선별하는 방법이 문맥적으로 떨어진 사진들을 선택하는데 매우 효율적임도 확인했다. 또한 제안한 알고리즘을 사용한 가상현실 기반의 인지재활 시스템을 제시한다. As the dementia elderly increase due to aging, socio-economic costs have increased greatly and research is being done to solve this problem.. This paper proposes a virtual reality-based cognitive rehabilitation system using image recognition technology and clustering algorithm by collecting pictures reflecting memories and memories of subjects. It is distinguished from existing methods in that it is a converged content that reproduces individual experiences and memories in the virtual reality space by using existing objective photos or pictures. We evaluated the effectiveness of the proposed clustering algorithm using 2022 photographs as an experimental data set. By expressing images with semantic-based word vectors, we confirmed that contextually similar photographs were clustered. We also found that the method of selecting photos to maintain the minimum distance from the Gaussian mixture model is very efficient for selecting contextually separated photos. In addition, a virtual reality-based cognitive rehabilitation system using the proposed algorithm is presented. KCI Citation Count: 1